Prinsip Kelakar pada Konten Dakwah Kanal Youtube Pemuda Tersesat - Vivi Intan Pangestuti; Asep Muhyidin; Dase Erwin Juansah (Departement of Mathematics Education, 2024)
This study aims to analyze and classify the utterances that contain the principle of levity and the violation of the maxims of politeness in the dakwah content of the Youtube channel of the Lost Youth. The qualitative research method used is the technique of listening, recording, and free listening (SBLC). This research describes the speech that raises the principle of joking through the violation of the maxims of politeness in oral pragmatics studies. The data is taken from the lost youth content from April 2021 to May 2021. The data selection criteria include all utterances in that period and are classified based on violations of politeness maxims that produce the principle of levity. The results showed 69 data on violations of the maxims of politeness, all of which resulted in the principle of levity, with details of 3 violations of the maxim of wisdom, 2 violations of the maxim of generosity, 52 violations of the maxim of respect, 6 violations of the maxim of simplicity, 4 violations of the maxim of agreement, and 2 violations of the maxim of sympathy. The Lost Youth YouTube channel uses jokes in various forms such as analogies, comparisons, and hyperbole to attract the audience's attention, make the da'wah message more interesting, and create a relaxed atmosphere. In conclusion, the violation of the maxims of politeness containing jokes in the lost youth's da'wah content is not only acceptable to the audience, but also effective in conveying religious messages.